ANALISIS RASIO KEUANGAN UNTUK MENILAI PERTUMBUHAN PERUSAHAAN (pada perusahaan PT. Gudang Garam Tbk. Kediri) - hendra kusuma (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2015)
The successof a companyin its effortsto bemore easilymeasured throughfinancial ratio analysis.Withfinancial ratio analysiswill be knownthe growth ofthe company.The financialhealthof a companyis one manifestationofthe company's overallperformanceshould beaddressed seriouslybythe company.Becauseahealthy companyin thefinancial, the company's growthcan be seenclearly. Todetermine the extent ofthe growthof a company, it can be preparedfinancial statementsincludethe balance sheetand profit andlossshouldbeaccounted fortruthand supportedbygood financialratio calculation.